Assessment of Occupational Burnout among Intensive Care Unit Staff in Jazan, Saudi Arabia, Using the Maslach Burnout Inventory - Abdullah Shbeer; Mohammed Ageel (Critical Care Research and Practice)
Objective. ICU workers are among the healthcare staff exposed to high occupational burnout in their daily interactions with patients, especially during the COVID-19 pandemic. This study aimed to investigate the prevalence and risk factors of burnout among ICU staff in the Jazan region of Saudi Arabia. Methods. A cross-sectional study was conducted using the Maslach Burnout Inventory (MBI), which was distributed to ICU staff between August 1 and November 30, 2021. A total of 150 ICU workers were invited to participate in the study. Results. A total of 104 ICU staff responded to the survey (69% response rate), including 62 nurses, 30 physicians, and 12 respiratory therapists. Among the respondents, 63 (61%) were female and 41 (39%) were male. The mean scores for emotional exhaustion, depersonalization, and personal accomplishment were 22.44 ± 14.92, 9.18 ± 7.44, and 29.58 ± 12.53, respectively. The ICU staff at high risk of emotional exhaustion, depersonalization, and personal accomplishment were 36%, 28%, and 47%, respectively. The leading cause of burnout among ICU staff in the study was workload, and taking a vacation was the most cited coping mechanism for occupational burnout. Conclusion. ICU staff are at high risk of emotional exhaustion, depersonalization, and lack of personal accomplishment. Policymakers should implement regulations that ensure hospitals have adequate employees to reduce the workload that leads to occupational burnout.